Analysis of the oppression experienced by the main character in 'Sepasang Mata Dinaya Yang Terpenjara' by Ni Komang Ariani - Safitri, Lufia (Maliki Interdisciplinary Journal, 2024)
This research explores the forms of oppression experienced by the main character, Dinaya, in the short story "A Pair of Dinaya's Terpenjara Eyes" by Ni Komang Ariani. By utilizing Iris Marion Young's (1990) theory of oppression, this research identifies three main forms of oppression: marginalization, powerlessness, and verbal violence. Marginalization is clearly visible when Dinaya faces her family's expectations which limit her involvement in the world of work. Powerlessness is reflected in Dinaya's inability to make decisions in her career and life, as well as giving in to family pressure. Verbal violence is manifested through psychological violence carried out by Dinaya's mother, which also creates feelings of failure. This study is literary criticism research which refers to a study discussing the phenomena or content of a literary work (Dickinson, 2020). This research also investigates Dinaya's resistance to oppression, namely through protests against her mother's demands and her loss of respect for her husband. The study concludes that short stories effectively depict the challenges women face within family structures and the ways they attempt to assert their rights and equality. These findings contribute to a deeper understanding of women's oppression in the literature.